Concevoir la prévention d’un risque émergent : une démarche fondée sur les représentations et les activités - Catherine L’Allain; Sandrine Caroly; Éric Drais; Olivier Witschger (Perspectives Interdisciplinaires sur le Travail et la Santé)
The emergence of nanomaterials is producing major technological innovations in many business sectors. There are major scientific and economic issues concerning these new materials which give rise to important health and environmental questions. This article describes the ergonomic intervention carried out in an industrial company that was seeking to collectively construct a risk prevention approach to nanomaterials. The goal of this study was to understand the real prevention practices that were implemented to counter this emerging risk and explore the risk representations of the workers in connection with their work activities. The study also looked at how the mobilization of company stakeholders around the prevention approach and their experiences with work activities transformed their representations and created a debate about the rules, procedures, and guidelines to be established.